Autor, linguagem e personagem maduros? O funcionamento do efeito metafórico no discurso da crítica literária - Ongaratto, Aline Chaiane Vogt (2014)
In this paper we take the adjective "mature" as a regularity, scheduled in the intradiscourse of the criticism that Luís Augusto Fischer, when he deals with a work or author, in his column "Fishing", of the newspaper Zero Hora. Having as main objective the understanding of the discursive functioning of adjective "mature", we identified the operation of the metaphorical text effect where the critical discusses the work Barba Ensopada de Sangue, by Daniel Galera. The theoretical and methodological perspective that we adopt is bound to the Discourse Analysis founded in the work by Michel Pêcheux and Eni Orlandi. We selected 42 texts that circulated in the "Fishing" column signed by literary critic Luís Augusto Fischer, between the years 2010 and 2013, and we understood that the adjective "mature" was a regular subject in the discourse of literary-critical when dealing with works from writers already recognized and especially above 40 years old. However, the classification of a linked to the writer’s age suffers a slip of senses, by the metaphorical effect at the time the literarycritical subject deals about the Daniel Galera’s book, which has just over 30 years old. By assuming a sustained metaphor by the interdiscourse, we began to question: (i) as the "mature" produces metaphorical effects of the order of interdiscourse? (ii) how to give the slips and transfers of meaning of this brand in their different contexts of operation? We conclude that the adjective "mature" works in the critical "Barba ensopada de sangue" as illusion of completeness of the subjects and the senses. How different contexts of operation of that metaphor, we "the mature author", "the mature character" and "the mature language". By the way the literary critic organizes his ideas in the text to address a "mature author," we understand that your writing can be associated with the biographical literature-psychological model, developed in the nineteenth century. At the moment that the critic approaches the "character in the maturation process," we explicit a sense of relationship with the novels of training. Finally, in discussing the "mature language," Fischer takes the position of author of the Dicionário de Porto-Alegrês and states in the direction of establishing the Sulina Language, context in which works the illusion of completeness by the tongue.